KINERJA USAHA AGROINDUSTRI KELANTING DI DESA KARANG ANYAR KECAMATAN GEDONGTATAAN KABUPATEN PESAWARAN - Imelda Castarica Sagala; Muhammad Irfan Affandi; Muhammad Ibnu (Lampung University, 2013)
This study aims to analyze the performance and value added of kelanting agroindustry. Kelanting is kind ofsnack made from cassava. Karang Anyar Village Gedongtataan District of Pesawaran Regency was chosenas a research site. The respondents consisted of 25 actors in agroindustry of kelanting. Data collection wasconducted from July to August 2012. Methods of data analysis for (1) performance are reported netloss/profit, productivity, and capacity, and (2) value added is Hayami method. The results showed that: (1)Performance of kelanting agroindustry was good based on the R/C ratio of 1.24 (R/C > 1), the productivitywas 16.07 kg per HOK (>7.2 kg/HOK), and the capacity was 0.92 (>0.5). (2) Value added of kelanting wasRp1,184.02 per kilogram of cassava or 34.57 percent.